Corporate culture change: adaptive culture structuration and negotiated practice - Whiteley, Alma; Price, Christine; Palmer, Rod (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this paper is to present adaptive culture structuration, a new approach for theorizing and analyzing culture change and for creating an “adaptive cultural structurated learning environment”.Design/methodology/approach – Incorporating a case study in the financial sector the paper explores 12 employees' narrated accounts of living through a culture change initiative. A constructivist, interpretive, qualitative research study followed grounded theory principles. Organizational documentation provided secondary data. Semi structured interview data were analyzed using content analysis, constant comparison and theoretical sensitivity and were managed by ATLAS.ti software.Findings – Three themes emerged: respondents' investment of self, accepting the culture change initiative and its values; employees' epistemic analyses of the embedded value promises including experiencing a critical incident that interrupted managers' enactment of values; employees' resulting “received practice” which represented the enacted (versus the espoused) values and was not visible to managers.Practical implications – An adaptive culture structurated learning environment fosters a relationship of “negotiated practice” instead of “received practice” between managers and employees in the constitution of corporate culture change. In this space, employee interpretations and assessments, which may otherwise remain hidden from managers and thereby prevent workplace learning opportunities, can be drawn upon, shared meaning co-produced and psychological contract issues explained.Originality/value – While much has been written on espoused culture change, this is the first theoretical model to examine the process from an employee perspective through an adaptive culture structurated lens.